ANALYZING YOUNG WOMEN’S MOTIVATING FACTORS TO BECOME ENTREPRENEURS IN NORTH SULAWESI (STUDY ON WOMAN UNIVERSITY STUDENTS IN MANADO) - Karinda, Farlansa Y.; Saerang, David P.E; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: The research objective are: to analyze various factors that motivates young women to become entrepreneur in North Sulawesi. This research type is causal uses quantitative type of research. This study is conducted in Faculty of Economics and Business Sam Ratulangi University at Manado. This research was held at 2018. This research use university students as respondents. Sample of this research are 60 respondents. Data analysis using validity and reliability test and regression analysis and hypothesis test. This research finding are: based on the results of hypothesis testing in particular the model of the research found that the research model consisting of: need for achievement, need for affiliation, need for autonomy, and need for domination simultaniouslly and partiallya has a positive and significant influence on motivation to become woman entrepreneur. Suggestions are: for women who are interested in becoming entrepreneurs, they must pay attention to various things that can motivate themselves to become entrepreneurs, including need for achievement, need for autonomy, need for autonomy and need for need for domination; the government and related parties in encouraging gender-based entrepreneurs or women to become new entrepreneurs must pay attention to the findings of this research where it is necessary to encourage motivation to become entrepreneurs among women, namely need for achievement, need for affiliation, need for autonomy and need for need for domination. Keywords: motivation, women entrepreneur, need for achievement, need for affiliation, need for authority, need for domination, university students, Manado